2020
DOI: 10.1038/s41598-020-72878-8
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid sTREM2 in Alzheimer’s disease: comparisons between clinical presentation and AT classification

Abstract: Triggering receptor expressed on myeloid cells 2 (TREM2) is an innate immune receptor expressed by microglia. Its cleaved fragments, soluble TREM2 (sTREM2), can be measured in the cerebrospinal fluid (CSF). Previous studies indicate higher CSF sTREM2 in symptomatic AD; however most of these studies have included biomarker positive AD cases and biomarker negative controls. The aim of the study was to explore potential differences in the CSF level of sTREM2 and factors associated with an increased sTREM2 level i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 50 publications
2
36
1
1
Order By: Relevance
“…Furthermore, its ectodomain is cleaved in the cell surface and shed at the plasma membrane, thus releasing a soluble fragment (sTREM2) which can be measured in the CSF as an indicator of microglial activity [78][79][80]. As it is involved in the regulation of microglia dynamics, and the subsequent amyloid plaque formation and synaptic plasticity, increased levels of sTREM2 within the CSF have been related to a protective response against AD pathology, thus serving as a potential biomarker [80][81][82][83]. On the other hand, YKL-40, the inflammation-related glycoprotein known as chitinase-3-like protein 1, breast regression protein 39, human cartilage glycoprotein 39 or chondrex, belongs to the family of chitinase-like proteins, but lacks the enzymatic activity of chitinases [84,85].…”
Section: Cerebrospinal Fluid Biomarkersmentioning
confidence: 99%
“…Furthermore, its ectodomain is cleaved in the cell surface and shed at the plasma membrane, thus releasing a soluble fragment (sTREM2) which can be measured in the CSF as an indicator of microglial activity [78][79][80]. As it is involved in the regulation of microglia dynamics, and the subsequent amyloid plaque formation and synaptic plasticity, increased levels of sTREM2 within the CSF have been related to a protective response against AD pathology, thus serving as a potential biomarker [80][81][82][83]. On the other hand, YKL-40, the inflammation-related glycoprotein known as chitinase-3-like protein 1, breast regression protein 39, human cartilage glycoprotein 39 or chondrex, belongs to the family of chitinase-like proteins, but lacks the enzymatic activity of chitinases [84,85].…”
Section: Cerebrospinal Fluid Biomarkersmentioning
confidence: 99%
“…Presence of mixed pathology and the differences in recruitment biases to atypical AD should also be considered when comparisons are made between cohorts in longitudinal outcomes (Dubois et al, 2007;Pillai et al, 2016). It is likely these are some possible reasons behind significant differences in sTREM2 levels reported by prior studies across the AD spectrum (Kleinberger et al, 2014;Gispert et al, 2016b;Henjum et al, 2016;Bekris et al, 2018;Suárez-Calvet et al, 2019;Knapskog et al, 2020).…”
Section: Limitationsmentioning
confidence: 99%
“…Clinical reports regarding cerebrospinal fluid (CSF) levels of sTREM2, a soluble TREM2 protein fragment produced by the cleavage of TREM2, have demonstrated varying levels of this protein in the different stages of AD (Wunderlich et al, 2013 ). Although most studies have shown that CSF sTREM2 is increased in the presence of AD biomarkers, the results are somewhat inconsistent regarding sTREM2 levels in amyloid-positive (A+) and tau-positive (T+) cognitively normal (CN) individuals (Ewers et al, 2019 ; Suárez-Calvet et al, 2019 ), patients with mild cognitive impairment (MCI) (Gispert et al, 2016b ; Henjum et al, 2016 ; Suárez-Calvet et al, 2016b , 2019 ; Ewers et al, 2019 ; Knapskog et al, 2020 ), and those with AD dementia (Gispert et al, 2016b ; Piccio et al, 2016 ; Suárez-Calvet et al, 2016b , 2019 ). Some studies have demonstrated no differences in sTREM2 levels across the AD spectrum (Gispert et al, 2016a ; Henjum et al, 2016 ; Knapskog et al, 2020 ), whereas other research has demonstrated decreased levels of sTREM2 in patients with AD dementia, perhaps partially reflecting the variability in clinical symptoms even within the same stage of AD (Kleinberger et al, 2014 ; Bekris et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…sTREM2 tem seu nível elevado já na fase présintomática, e foi visto aumento de 18%-23% em indivíduos em estado demencial 41 , porém aparenta ter seu pico na fase prodrômica, o que seria uma limitação para seu uso, complicando o desenvolvimento de um ponto de corte clínico 31,58 . Uma forte associação foi observada entre sTREM2 e a idade, patologia tau, YKL-40 e injuria neuronal, mas pouca ou nenhuma com níveis de Aβ 21,26,28,35,41,58 . No estudo de Henjum et al 27 , entretanto, só foi vista a correlação entre sTREM2, t-tau e p-tau em LCR no grupo de controles saudáveis, e não nos grupos com CCL ou DA, usando um novo ELISA foi desenvolvido para esse estudo.…”
Section: Trem2unclassified